Rodinný dům s provozovnou - Flousek, David (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Téma bakalářské práce je novostavba rodinného domu s provozovnou v Machově. Objekt je zasazen do mírně svažitého terénu. Má dvě nadzemní a jedno podzemní podlaží. Budova je navržena ze systému Porotherm P+D a stropní konstrukce ze systému Porotherm strop. Konstrukce střechy je plochá.

The theme of bachelor´s thesis is new-building family house with establishment in Machov. The building is set in a slighty sloping terrain. It has two overground floors and basement. The building is designed of system Porotherm P+D and ceiling construction of system Porotherm ceiling. The roof strukture is a flat roof.
Family House with an establishment
Keywords: Rodinný dům; provoz; servis; Family house; plant; service